The Mediating Role of Perceived Organizational Prestige in the Relationship Between Communication Climate and Organizational Identity (Third Sector Social Economic Review, 2025)
In today’s competitive environment, sustaining a long-term competitive advantage requires not only strategic resources but also the emotional bond and sense of ownership that employees develop toward their organizations. In this context, the internal communication climate stands out as a key factor shaping employees’ attitudes and behaviors toward the organization. Although the effect of communication climate on organizational identification has been widely addressed in the literature, studies examining other psychological or perceptual variables that may influence this relationship remain limited. In particular, the role of perceived organizational prestige in this dynamic has not been sufficiently explored. This study aims to investigate the effect of perceived organizational prestige on the relationship between communication climate and organizational identification. To this end, a quantitative study was conducted with data collected from 677 employees working in 12 companies operating in the defense industry in Ankara, Turkey. The findings indicate that a positive communication climate significantly enhances organizational identification, and this effect becomes stronger depending on the level of prestige employees attribute to their organization. The results offer both theoretical and managerial contributions. Especially in strategically important sectors such as defense, strengthening the communication climate and consciously managing organizational prestige play a critical role in enhancing employee commitment.
Keywords: Communication Climate; Organizational Identification; Organizational Prestige; Defense Industry; Structural Equation Modeling